2009
DOI: 10.1164/rccm.200903-0328oc
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-14 Mediates a Phenotypic Shift in the Airways to Increase Mucin Production

Abstract: Rationale: Induced mainly by cigarette smoking, chronic obstructive pulmonary disease (COPD) is a global public health problem characterized by progressive difficulty in breathing and increased mucin production. Previously, we reported that acrolein levels found in COPD sputum could activate matrix metalloproteinase-9 (MMP9). Objectives: To determine whether acrolein increases expression and activity of MMP14, a critical membrane-bound endopeptidase that can initial a MMP-activation cascade. Methods: MMP14 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 91 publications
(115 reference statements)
0
41
0
2
Order By: Relevance
“…Two groups reported that loss of Smad4 in the Kras G12D background causes IPMNs in the majority of mice (32, 35). Even though it is not clear why MT1-MMP expression results in lesions with mucin production, it is interesting to note that MT1-MMP in the airways can induce a phenotypic shift to increase mucin production and can also proteolytically cleave the membrane bound mucins from the surface of epithelial cells (43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…Two groups reported that loss of Smad4 in the Kras G12D background causes IPMNs in the majority of mice (32, 35). Even though it is not clear why MT1-MMP expression results in lesions with mucin production, it is interesting to note that MT1-MMP in the airways can induce a phenotypic shift to increase mucin production and can also proteolytically cleave the membrane bound mucins from the surface of epithelial cells (43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…TAPI-2-insensitive MMP-14 has been identified as sheddase of syndecan-1, and this effect was inhibited by TIMP-2 expression [31,32]. Decreased expression of TIMP-2 mRNA has previously been reported in COPD versus control lung tissue [38] along with increased MMP-14 levels and/or activity in COPD patients [8]. We observed that TIMP-2 levels were significantly lower in PBECs from COPD than from healthy non-smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-14 together with MMP-9 activity increases in COPD sputum; in particular, MMP-14 expression is induced in mucin production in COPD (Deshmukh et al, 2009). …”
Section: Tumorigenesismentioning
confidence: 99%